Концептуализация понятий “моральная экономика” и “экономическая мораль” в исторической и социологической науке - Кондратик, Л. (Социология: теория, методы, маркетинг, 2008)
The paper analyzes two notions elaborated within historiography and sociology, such as “moral economy” and “economic morality”. New opportunities for interdisciplinary dialogue are also сonsidered. The fundamental difference between moral economy in traditional and modern societies is conceptualized with regard to the works of E.C.Ban field, J.Habermas, K.Polanyi, H.S.Becker, D.North, N.Luhmann and R.Ingle hart.